The The Relationship between Aerobic Exercise and Blood Sugar Levels and Blood Pressure in Patients with Type 2 Diabetes Mellitus - Farita Adhynda Amithya; Dwi Rosella Komalasari; Safari Wahyu Jatmiko; Agus Widodo (Jurnal KESANS : Kesehatan dan Sains, 2025)
Introduction: Diabetes mellitus and hypertension are degenerative diseases with a high prevalence in the elderly population and commonly occur together as comorbidities, contributing to worsening metabolic and cardiovascular conditions. The coexistence of these diseases increases the risk of serious metabolic complications. Aerobic is a recommended non-pharmacological intervention because it helps control blood glucose levels, improves insulin sensitivity, and reduces blood pressure through mechanisms that enhance endothelial function and cardiorespiratory capacity. Objective: This study aims to analyze the relationship between aerobic activity levels and the status of diabetes mellitus and hypertension in elderly individuals diagnosed with type 2 diabetes mellitus in the community. Method: An analytical observational study with a cross-sectional design. Result and Discussion: The Mann-Whitney test showed a significant association between aerobic activity and diabetes mellitus status (p = 0.001), indicating that lower aerobic levels were associated with higher glucose levels. Aerobic activity was also significantly associated with hypertension status (p < 0.001), showing that lower aerobic increased the likelihood of elevated blood pressure. Conclusions: Increasing aerobic activity is an important non-pharmacological strategy to manage metabolic and cardiovascular risks in older adults with diabetes, and should be integrated into structured community health programs.